Control of mini autonomous surface vessel - Zainal Abidin, Zulkifli; Arshad, Mohd Rizal; Ngah, Umi Kalthum; Ping, Ong Boon (2010)
This paper presents an initial development stage of mini Autonomous Surface Vehicles (ASVs). The ASVs named Drosobot is being developed for hydrographic survey on lakes. The paper also explains the factors influencing the conceptual model, the selection of shape, the parameters influencing the control in the design, the practicalities encountered in navigational issues and mechanisms of communication amongst a group of these ASVs based upon the Drosophila